Diversity of Migratory Shorebirds and their Habitat Characteristics in Kuala Gula Bird Sanctuary, Perak, Malaysia - Lomoljo, Romeo M. (2011)
The research study was conducted in one of the primary corridors and stopover sites of the migratory shorebirds during annual migrations in Kuala Gula Bird Sanctuary, Perak in the west coast of Peninsular Malaysia. The objective were to determine the diversity of migratory shorebirds and to assess the habitat quality, prey availability, environmental conditions, heavy metal concentrations in the sediments, macrobenthic organisms, fish and shrimps from October 2006-September 2007. Two sampling stations each covering an area of 100 x 100 m, were established to represent the whole Kuala Gula Bird Sanctuary between 04º55.185’N, 100º27.8’E and 100º27.761’E. Survey of shorebirds was carried out through direct count and identification to species level. Sixty-one migratory shorebird species from 12 families were identified in both stations. The overall total of shorebirds density was found to be higher in northward migration (7913 individual/ha) than southward migration (4396 individual/ha). Similarly, the species diversity index (H’ = 3.20; p<0.05) and the species richness (d’ = 6.19; p<0.05) were also higher in northward migration. However, no significant (p>0.05) differences were found in species evenness, between southward and northward migration throughout the study period. Meanwhile, 28 species of macrobenthos in both stations were recorded and identified representing 15 families throughout the study period. The species diversity index of macrobenthos were higher (p<0.05) in station 2 (H’= 3.24) compared to station 1 (H’= 3.13). Similarly, the species richness was higher (p<0.05) in station 2 (d’= 6.22) compared to station 1 (d’ = 6.11). Among the macrobenthos, polychaetes were found to be the most abundant (204.3 ± 6.84 individual/m2), followed by molluscs (156.8 ± 6.3 individual/m2), fishes (132.8 ± 6.6 individual/m3), and shrimps (135.3 ± 4.1 individual/m3). The overall total macrobenthos density and biomass revealed a positive (r = 0.920; p<0.05) correlation with bird density, suggesting the importance of food resources to the distribution of migratory shorebirds in the area. The environmental quality in the area in terms of water quality and nutrients were maintained in healthy levels. No significant variations in the in situ water quality parameters (salinity, pH, temperature and dissolved oxygen) were observed in both sampling stations throughout the study period. In addition, nitrate nitrogen (NO3-N), total ammonia nitrogen (TAN) and soluble reactive phosphorus (SRP) in the water surface were all in safe levels and maintained at minimum (SRP = 55.92 ± 7.88 μg/L; nitrate-N = 85.68 ± 24.33 μg/L; TAN = 85.91 ± 6.54 μg/L) throughout the study period. The total geochemical fractionation analysis of sediments in Station 1 and Station 2 ranged from 80.4 - 91.3%, 61.9 - 86.4%, 49.4 - 72.4%, 61.3 - 96% and 63 - 95% of the total Cd, Cu, Ni, Pb and Zn were accumulated in the ‘resistant’ fractions throughout the sampling period which indicated that the mobility of these metals in Kuala Gula coastal water were low in terms of contribution or contamination from anthropogenic sources. Significant (p<0.05) and positive correlation were detected between (r = 0.578) birds density and Pb metal concentration of sediments in station 2. However, the total fraction of Cu (r = -0.591 and Ni (r = -0.513) in sediments had significant p<0.05) negative correlation with crabs density in station 1. Similarly, the Pb (r = 0.657) metal concentrations in sediments was significantly p<0.05) correlated to shrimp density in station 1. Meanwhile, positive correlation, with lesser confidence (p<0.05) was also detected between mollusc density and Cd (r = 0.492) metal concentrations in station 2. Overall, this study revealed that Kuala Gula ecosystems are still pristine with low anthropogenic sources, abundant food supply and ideal habitat for migratory shorebirds. Therefore, Kuala Gula coastal water is still in healthy condition but continuous environmental monitoring program should be implemented before it reaches alarming level as the ever increasing human activities and rapid developments in many infrastructures and industry sectors are continuously expanding. At present, the results of the study will provide important baseline data as reference for future studies on migratory shorebirds.